2022
DOI: 10.21037/jtd-21-1938
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of surgical treatment for high-grade neuroendocrine carcinoma of the lung: a multi-institutional retrospective study

Abstract: Background: High-grade neuroendocrine carcinoma (HGNEC) of the lung, which includes small cell lung cancer (SCLC) and large cell neuroendocrine carcinoma (LCNEC), is an aggressive form of lung cancer.Although lobectomy followed by adjuvant chemotherapy is regarded as the standard therapy for this disease, it would be an uphill struggle for HGNEC patients to receive that multidisciplinary therapy perfectly. This study aimed to examine recurrence and survival outcomes in surgically treated patients with HGNEC of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Achieving microscopically negative margins is essential, with completeness of resection among the strongest positive prognostic indicators for these aggressive tumors. A study by Haruki et al found lobectomy or more plus mediastinal lymph node dissection and adjuvant chemotherapy provided better pHGNEC outcomes than limited treatment [ 24 ]. However, we found worse prognosis for patients undergoing complex or combined lobectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving microscopically negative margins is essential, with completeness of resection among the strongest positive prognostic indicators for these aggressive tumors. A study by Haruki et al found lobectomy or more plus mediastinal lymph node dissection and adjuvant chemotherapy provided better pHGNEC outcomes than limited treatment [ 24 ]. However, we found worse prognosis for patients undergoing complex or combined lobectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Among lung cancers, neuroendocrine carcinoma is not a common pathological type, mainly including small-cell carcinoma, combined small-cell carcinoma, large-cell carcinoma, and large-cell neuroendocrine carcinoma (LCNC) [ 2 , 3 ]. As for LCNC, its treatment is now considered to be closer to that of small-cell carcinoma [ 4 ]. Surgical resection has been shown to be effective for limited-stage small-cell lung cancer, but the role of surgery for large-cell neuroendocrine carcinoma still needs further clarification [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%